EVALUATING THE SAMR MODEL FOR ENHANCING ICT INTEGRATION IN ENGLISH LANGUAGE TEACHING AT THE TERTIARY LEVEL A SYSTEMATIC LITERATURE REVIEW - Benny Krisbiantoro; Imam Ahmad Ashari (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2024)
Significantly impacted education, necessitating effective integration into teaching practices. This study examined the application of the Substitution, Augmentation, Modification, and Redefinition (SAMR) model to evaluate ICT integration in English Language Teaching (ELT) at the tertiary level. The research aimed to determine whether the SAMR model could enhance pedagogical practices beyond mere technology substitution and how it compared with the Technological Pedagogical Content Knowledge (TPACK) model. This study addressed the issue of stagnant ICT integration in ELT, hypothesizing that the SAMR model provided a more robust framework for transformative technology use compared to the TPACK model. The study’s purpose was to assess the SAMR model’s effectiveness in advancing ICT integration in university-level ELT. Objectives included comparing SAMR with TPACK and identifying barriers to effective ICT use. A systematic literature review was conducted using six electronic databases covering the past decade (2013-2023). The review followed PRISMA guidelines with defined inclusion and exclusion criteria. Preliminary results revealed that while the SAMR model offered the potential for enhancing teaching practices, many educators remained at the substitution stage, mainly replacing traditional methods with technology without significant pedagogical changes. Challenges included insufficient training, institutional resistance, and lack of support. The findings underscored the need for extensive training, supportive policies, and continued research to improve ICT integration in higher education. This study contributes to understanding effective technology integration and provides recommendations for institutions seeking to elevate their teaching practices through meaningful ICT adoption. This research offers insights and practical recommendations for enhancing technology integration in higher education, focusing on overcoming current limitations and advancing teaching methodologies through the SAMR model.